Application of intraoperative infrared thermography in bypass surgery for adult moyamoya syndrome: A preliminary study - Lin, Jinghui; Wu, Yiwen; Deng, Xinpeng; Zhou, Shengjun; Liu, Yuchun; Zhang, Junjun; Zeng, Yiyong; Li, Xianru; Gao, Xiang; Xu, Bin; Zhou, Chenhui (Frontiers in Neurology, 2023)
Background and Objectives: Cerebral revascularisation surgery is the mainstay of treatment for moyamoya syndrome (MMS) today, and intraoperative determination of the patency of the revascularized vessel is a critical factor in the success of the procedure. Currently, major imaging modalities include intraoperative indocyanine green (ICG) videoangiography (ICG-VA), digital subtraction angiography (DSA), and vascular ultrasound Doppler. Infrared thermography is a modern imaging modality with non-contact devices for the acquisition and analysis of thermal data. We aimed to investigate the feasibility and advantages of infrared thermography in determining anastomotic patency during MMS surgery. Methods: ICG-VA and infrared thermography were performed simultaneously in 21 patients with MMS who underwent bypass surgery. The detection result of vessel patency was compared, and the feasibility and advantages of infrared thermography were assessed. Results: The patency of the anastomosis was accurately determined in 21 patients using either ICG angiography or infrared thermography. In 20 patients, the results of infrared thermography showed that the vascular anastomosis was unobstructed, and there was an agreement with the subsequent results of ICG-VA. In one patient, we suspected inadequate patency after testing the anastomosis with infrared thermography, and the results of ICG-VA evaluation of the anastomosis confirmed that there was indeed an anastomotic obstruction. Conclusion: Compared with ICG-VA, infrared thermography is equally effective in assessing anastomotic patency and avoids the problems of drug allergy, retention, and inability to repeatedly assess the anastomosis caused by ICG-VA.